Roman-Gothic Foedus in the 3rd and 4th Century Sources - Križič, Ivan (Historical Thought, 2024)
This paper explores the complex relationship between the Roman empire and Gothic people from 238 to 382 C.E., focusing on the classification and understanding of Roman-Gothic foedus agreements. By analyzing primary sources such as Ammianus Marcellinus, Jordanes, Zosimus, Procopius and others, the paper wants to reassess whether these agreements can be accurately termed foedus, in the clasical meaning of the word, given their distinct characteristics and historical contexts. The research highlights the evolving dynamics of power between the Roman Empire and Goths, their military alliances, negotiation, identity, and mutual dependency, alongside the roles of the Roman empire and Gothic communities during this period. Ultimately, the author argues for a deeper understanding of these treaties as forms of control rat her than purely diplomatic agreements, but at the same time, understanding their conected tradition, challenging longstan ding generaly one-sided and superficial scholarly interpretations.